2022
DOI: 10.1158/1538-7445.am2022-3324
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3324: Optimizing the therapeutic potential of tyrosine kinase inhibitors in chemo-immunotherapy of B-cell acute lymphoblastic leukemia involving rituximab

Abstract: B-cell acute lymphoblastic leukemia (B-ALL) is a malignancy caused by accumulation of immature B cells. Advances in the field, especially in genomic studies and new treatment development, significantly improved the prognosis of B-ALL over the last decades. However, the B-ALL subtype harboring Philadelphia chromosome t(9;22)(q34;q11) (Ph+ B-ALL) still remains a therapeutic challenge despite available targeted treatment with tyrosine kinase inhibitors (TKIs). The novel therapeutic regimens for adult B-ALL often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Data on ASCI in combination with NK cell-based immunotherapy are scarce. Domka et al showed similar results in B-ALL cell lines and in xenografts with NSG mice and primary patient B-ALL cells [5]. Consistent with our data, DASA and PONA inhibited NK cell function, whereas ASCI did not.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Data on ASCI in combination with NK cell-based immunotherapy are scarce. Domka et al showed similar results in B-ALL cell lines and in xenografts with NSG mice and primary patient B-ALL cells [5]. Consistent with our data, DASA and PONA inhibited NK cell function, whereas ASCI did not.…”
Section: Discussionsupporting
confidence: 92%
“…CD20 expression itself is a negative prognostic marker in adult B-ALL [31] and CD20 positivity is generally defined as CD20 expression in >20% of blasts. A recent study suggests increased CD20 expression in BCR-ABL1 positive cases [5]. The addition of 16-18 doses of rituximab to multi-agent chemotherapy in a clinical trial by the GRAALL group comprising 209 patients with CD20 positive B-ALL resulted in significantly prolonged event-free survival [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation